A Study to Compare the Stress Patterns in the Edenulous Mandibalur Bone Around the Two Implant Retained Over Denture and the Prosthesis Restored with All-On-Four Concept Using the Three Dimensional Finite Element Analysis - Puneeth Hegde1, Satish Shenoy2, Shobha Rodrigues3, Thilak Shetty4, Umesh Pai1, Sharon Saldhana1, Mah (Indian Journal of Forensic Medicine & Toxicology, 2020)
When we consider the rehabilitation of patients with the mandibular implant supported over denture, the influence of the implant number and the cantilever design on the stress distribution on the bone needs to be assessed precisely.Purpose: The purpose of the simulation study was to compare the biomechanical behavior of the two implant supported over denture design with the All-On-Four Concept using the three dimensional finite element method thereby evaluating the Von Misses stresses induced on the implant under different loading simulations.Materials & Method: Three dimensional models representing mandible restored with two implant supported prosthesis was compared with the models that were restored based on the ‘All-On-Four’ concept. The models were then subjected to four different loading simulations (full mouth biting, canine disclusion, load on cantilever, and load in the absence of cantilever). The maximum von Mises stresses were localized and quantified for comparison.1Results: Among the models, under all loading simulations, the maximum stress concentrations were along the neck of the implant. The stress levels for full mouth loading simulation was highest for two implant supported overdenture design and the least for All-On-Four overdenture design. In all the designs, the least stress was when the implants were loaded in a lateral direction. The stress levels for cantilever and non-cantilevered designs were nearly the same for all the simulated designs.Conclusion: When tested under different loading simulations, both models showed similar location and distribution of stress patterns. Thus from the study it can be concluded that the All-On-Four Concept is a clinically applicable treatment option for the atrophic edentulous ridges and induces least amount of stresses on the edentulous ridges. Therefore the overall longevity of the prosthesis is greatly enhanced.